2023
DOI: 10.1007/s40789-022-00562-5
|View full text |Cite
|
Sign up to set email alerts
|

Master crack types and typical acoustic emission characteristics during rock failure

Abstract: Acoustic emission (AE) signals contain substantial information about the internal fracture characteristics of rocks and are useful for revealing the laws governing the release of energy stored therein. Reported here is the evolution of rock failure with different master crack types  as investigated using Brazilian splitting tests (BSTs), direct shear tests (DSTs), and uniaxial compression tests (UCTs). The AE parameters and typical modes of each fracture type were obtained, and the energy release characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The loading system used in the test is RLJW-2000 rock servo pressure testing machine. 27 Before formal loading, preload the sample to ensure full contact between the indenter and the sample. The contact line of the upper indenter is symmetrical in the center of the sample.…”
Section: Three Point Bending Test Of Different Coal and Rock Mediamentioning
confidence: 99%
“…The loading system used in the test is RLJW-2000 rock servo pressure testing machine. 27 Before formal loading, preload the sample to ensure full contact between the indenter and the sample. The contact line of the upper indenter is symmetrical in the center of the sample.…”
Section: Three Point Bending Test Of Different Coal and Rock Mediamentioning
confidence: 99%
“…The AE signals released during the compression of granite specimens are closely associated with the formation and propagation of microcracks [44][45][46][47][48]. The characteristics of temporal AE sequences for granite specimens under different confining pressures are depicted in Figures 11-13 Combined with the stress-strain curves, it can be observed that the AE count characteristics of granite specimens under different immersion conditions are generally similar during the deformation and failure processes.…”
Section: Time Domain Characteristics Of Ae Countsmentioning
confidence: 99%
“…AE frequency domain characteristics can be used to analyze the fracture process and to identify fracture precursor information of rocks [44,45]. The evolution characteristics of the peak frequency distribution of granite specimens under different chemical corrosion conditions are shown in Figures 14-16.…”
Section: Ae Frequency Domain Characteristicsmentioning
confidence: 99%
“…Zhao and Liu [ 18 ] discovered that the cumulative AE energy suddenly increases before reaching peak strength, correlating positively with the development of penetrating cracks. Zhao et al [ 19 ] obtained AE parameters and typical modes for different fracture types, discussing the energy release characteristics of each fracture mechanism. Lei et al [ 20 ] through a series of loading and unloading experiments on surrounding rocks, found that the spatial distribution of AE events is related to the stress state and structure of the specimens.…”
Section: Introductionmentioning
confidence: 99%